Izkustvo tujega in responzivnost v Cankarjevem romanu Tujci - Leskovec, Andrea (Jezik in slovstvo, 2020)
The paper deals with Ivan Cankar's novel Tujci, which has not yet been the subject of extensive analysis. The novel's main motif is foreignness, which is portrayed in many ways and is the result of perception. The protagonist Pavle Slivar experiences himself as an outcast and projects his sense of foreignness to the outside world. This creates a kind of vacuum in which he is a stranger and experiences others as strangers. In this space of alienation, there is no responsive treatment of the other, nor is there perception of the other/the foreign. The reason for this must be sought in the various centrisms that direct the perception of the other/the foreign and in the concept of the subject on which Cankar's novel is based. In the analysis, we turn to the theory of responsiveness of phenomenologist Bernhard Waldenfels.
Keywords: Cankar, Ivan; foreignness; perception of the other/the foreign; responsiveness; responzivnost; Slovene literature; slovenska književnost; tujost; Waldenfels, Bernhard; zaznavanje tujega/drugega